Introducing the wiiw COMECON Dataset - Monika Schwarzhappel; Artem Kochnev; Isilda Mara; Magdalena Frei; Alexandra Bykova; Hana Ruskova; Renate Prasch; Xhesika Banushi (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper introduces the historical dataset with economic time series of socialist Bulgaria, Czechoslovakia (CSSR), the German Democratic Republic (GDR), Hungary, Poland, Romania, the Soviet Union (USSR) and Yugoslavia from 1944 to 1993 as well as a new dataset on Albania created as part of this project. The paper explains the dataset's structure and gaps as well as the harmonisation efforts and accounting methodologies adopted in the member countries of the Council of Mutual Economic Assistance (CMEA or COMECON) during that period. The paper serves as a companion for the users of the wiiw COMECON Dataset.
Keywords: B22; B24; B27; B40; B41; N14; N34; N44; N54; N64; N74; P20; P30; P51; 330; CMEA; COMECON; socialist countries; Albania; Bulgaria; CSSR; GDR; Hungary; Poland; Romania; Soviet Union; Yugoslavia; population; net material product; GDP; investment; labour market; prices; wages; production; consumption per capita; budget; trade by partners; trade by commodities and regions; conversion factors; external finance; economic history; comparative economic systems; historical dataset of economic time series